Effect of Topical Corticosteroid Treatment on microRNA Expression in Infants with Atopic Dermatitis - Janna Nousbeck; Maeve A. McAleer; Elaine M. Kenny; Alan D. Irvine (JID Innovations, 2025)
MicroRNAs (miRNAs) have been implicated in a variety of disorders. Although studies have examined miRNA in pediatric atopic dermatitis (AD), the impact of topical corticosteroid (TCS) therapy on miRNA expression in pediatric AD has not been investigated. We sought to investigate the effects of 6 weeks of TCS therapy on miRNA expression in infants with AD. Small RNA sequencing and real-time RT-qPCR were performed to identify differentially expressed miRNAs in PBMCs of infants with AD after TCS treatment; HTG EdgeSeq was used to identify differentially expressed miRNAs in plasma. Kyoto Encyclopedia of Genes and Genomes pathway enrichment analysis was conducted using a list of experimentally verified miRNA targets sourced from the DIANA-TarBase and miRTarBase databases. Five miRNAs were differentially expressed in circulating PBMCs after TCS treatment (miR-143-3p, miR-27a-5p, miR-126-3p, miR-451a, and miR-223-3p); 12 miRNAs were differentially expressed in plasma. These miRNAs have regulatory functions crucial for regulating cell growth and survival, vascular adhesion, angiogenesis, skin barrier integrity, stress and nervous system processes, immune responses, inflammation, and T helper 17 cell differentiation. TCS treatment led to a distinct miRNA expression profile in peripheral blood, providing insights into how this treatment impacts disease mechanisms in childhood AD.